Dampak Pandemic Covid- 19 Terhadap Indeks Pembangunan Ekonomi Inklusif Jawa Timur Indikator Tingkat Kemiskinan Dan Ketimpangan - Rahmawati, Anis; Lutfiani, Layna; Yunia, Zulvita Rahma; Rofiqoh, Isma'iddatur; Zahrok, Fitri Fatimatuz; Wahyuningtyas, Destiana (Universitas Nusantara PGRI Kediri, 2021)
This research uses descriptive quantitative approach. The purpose of this research is to find out how the Covid 19 pandemic affects the inclusive economic development index. To conduct this research, the method used is quantitative method with statistical tests between dependent variables and independent variables in order to provide results that can be explained by numbers. It is based on data analysis and relevant data collection techniques obtained from previous studies and the official website that published the data. Sources of data in this study use secondary data. The data is in the form of documents and reports, which are in the form of an overview of the research location and data relevant to a study. Researchers used data collection techniques from various scientific journal literatures that were reviewed and processed. The results of the test show that there is a significant effect between Covid 19 on inclusive economic growth in East Java. Where the Covid-19 Virus pandemic has had a number of significant impacts in the domestic economic sector and on the existence of MSMEs in the country and nation. The impact of Covid-19, which has caused economic shock, also greatly affects the economy, both individually, micro, small, and medium enterprises, the country's economy which includes local, national and global levels.